Migalastat HCl Reduces Globotriaosylsphingosine (Lyso-Gb3) in Fabry Transgenic Mice and in the Plasma of Fabry Patients - Young-Gqamana, Brandy; Brignol, Nastry; Chang, Hui-Hwa; Khanna, Richie; Soska, Rebecca; Fuller, Maria; Sitaraman, Sheela A.; Germain, Dominique P.; Giugliani, Roberto; Hughes, Derralynn A.; Mehta, Atul; Nicholls, Kathy; et al. (PloS one, 2013)
Fabry disease (FD) results from mutations in the gene (GLA) that encodes the lysosomal enzyme α-galactosidase A (α-Gal A), and involves pathological accumulation of globotriaosylceramide (GL-3) and globotriaosylsphingosine (lyso-Gb3). Migalastat hydrochloride (GR181413A) is a pharmacological chaperone that selectively binds, stabilizes, and increases cellular levels of α-Gal A. Oral administration of migalastat HCl reduces tissue GL-3 in Fabry transgenic mice, and in urine and kidneys of some FD patients. A liquid chromatography-tandem mass spectrometry method was developed to measure lyso-Gb3 in mouse tissues and human plasma. Oral administration of migalastat HCl to transgenic mice reduced elevated lyso-Gb3 levels up to 64%, 59%, and 81% in kidney, heart, and skin, respectively, generally equal to or greater than observed for GL-3. Furthermore, baseline plasma lyso-Gb3 levels were markedly elevated in six male FD patients enrolled in Phase 2 studies. Oral administration of migalastat HCl (150 mg QOD) reduced urine GL-3 and plasma lyso-Gb3 in three subjects (range: 15% to 46% within 48 weeks of treatment). In contrast, three showed no reductions in either substrate. These results suggest that measurement of tissue and/or plasma lyso-Gb3 is feasible and may be warranted in future studies of migalastat HCl or other new potential therapies for FD.